Understanding Donor Behaviour: Actors and Processes in Disaster-Relief Decision-Making - Mamuji, Aaida (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2014)
Two of the largest natural disasters that hit in 2010 were the January earthquake in Haiti and the flooding in Pakistan which followed seven months later. Unlike Canada’s disaster-relief intervention to the earthquake, the response to the Pakistan floods has been argued to be comparatively minimal relative to the extent of damage sustained. Through a series of interviews with bureaucrats affecting Canada’s disaster-relief responses in both 2010 disasters, this paper asks, who (and what) really determines the scope and magnitude of international disaster-relief interventions? Through the development and application of a multi-level conceptual framework, donor behaviour is said to be affected by each of macro-institutional, meso-contextual and micro-foundational factors. The findings highlight the determinative role of political actors in shaping humanitarian assistance decisions.